Plunging Ranula (Right side): A Case Report (Medicine Today, 2013)
Plunging ranulas, also known as deep, diving, cervical or deep plunging ranula, usually appear in conjunction with oral ranula. Rarely, these ranulas may arise independent of oral swelling. A rare case of plunging ranula without oral swelling is discussed along with review of literature. DOI: http://dx.doi.org/10.3329/medtoday.v25i1.16074 Medicine Today 2013 Vol.25(1): 52-53